Recombinant thrombomodulin inhibits arterial smooth muscle cell proliferation induced by thrombin - Li, J; Garnette, C S; Cahn, M; Claytor, R B; Rohrer, M J; Dobson, Jr, J G; Gerlitz, B; Cutler, B S (Journal of vascular surgery, 2000)
Restenosis after angioplasty or bypass grafting to restore circulation to ischemic organs is still an unsolved problem. Thrombin generated in high concentrations at the sites of vascular injury plays a central role in thrombosis and hemostasis. alpha-Thrombin has also been implicated as a mitogen for smooth muscle cell (SMC) proliferation that contributes to arterial restenosis. Thrombomodulin has a high affinity of binding with thrombin and converts thrombin from a procoagulant to an anticoagulant. This study was designed to examine whether thrombomodulin could also moderate the thrombin-mediated SMC proliferative response. Porcine carotid artery SMCs (passages 4-7) were plated onto 96-well plates and incubated for 3 days. After growth arrest in a defined serum-free medium for 2 to 3 days, SMCs were subjected to the reagents as follows: (1) human alpha-thrombin, (2) recombinant human soluble thrombomodulin containing a chondroitin sulfate moiety, (3) thrombin receptor agonist peptide (SFLLRNPNDKYEPF), and (4) alpha-thrombin or thrombin receptor agonist peptide combined with recombinant thrombomodulin (rTM). The viability and proliferation status of SMCs were quantified with MTT (thiazolyl blue) mitochondrial function and bromodeoxyuridine (BrdU)-DNA incorporation assays. Human alpha-thrombin increased SMC proliferation in a dose dependent manner by more than 25% and 30% with thrombin 1 U/mL to 3 U/mL compared with control groups on day 7 (P <.006). rTM concentrations from 0.5 microg/mL to 3 microg/mL have no significant effect on SMC growth. The stimulation of SMC proliferation induced by alpha-thrombin at 0.5 U/mL, 1 U/mL, and 2 U/mL was significantly inhibited with rTM at 2 microg/mL and 3 microg/mL on days 3, 7, and 10 as evaluated with MTT assay (P <.01 to <.05) and BrdU-DNA incorporation assay on day 3 (P <.008). Thrombin receptor agonist peptide increased SMC BrdU-DNA incorporation at 48 hours (P <.007), and its effect was not altered by rTM. rTM containing all of the extracellular domains of thrombomodulin inhibits the effect of thrombin on SMC proliferation in vitro. Because thrombin is a mitogenic mediator of SMC in vascular injury, inhibition of its function in vivo could help to prevent SMC hyperplasia. The success of further studies in vivo may lead to use of rTM for decreasing or preventing arterial restenosis.